Core strength characteristics of Korean national amateur male boxers: A comparison with anaerobic power and maximal strength - Yoon, D.-H.; Kim, K.-J. (Exercise Science, 2019)
PURPOSE: We examined associations between core strength and anaerobic Power and maximal strength in Korean national amateur male boxers. METHODS: Cross-sectional associations between core strength were examined in 92 amateur elite boxers (mean age: 22.2± 2.60 years). Anaerobic power and maximal strength were obtained. Main outcome measures included Wingate anaerobic test and arm ergometer test and isokinetic knee strength and 1RM. RESULTS: Isokinetic trunk flexion and extension were associated with anaerobic power (upper and lower average power and peak power). In addition, trunk strength of flexion and extension were significantly associated with of maximal strength (Knee extension and flexion and 1RM). CONCLUSIONS: Isokinetic trunk strength revealed an association between anaerobic power and maximal strength. Future research addressing the contributions of the core strength could be conducted with the proper training program development in mind. Additionally, studies about the years of boxing training necessary to achieve an international competitive level and the common boxing-specific training used by Olympic-level boxers are needed.